Socioeconomic differences in the motivation to stop using e-cigarettes and attempts to do so. (June 2020) - Jahnel, Tina; Ferguson, Stuart G.; Partos, Timea; Brose, Leonie S.
Highlights: SES and motivation to stop using e-cigarettes may be associated. SES may predict attempts to stop using e-cigarettes. Further research on the social patterning of quitting vaping is needed. Abstract: Introduction: In England, the use of electronic cigarettes as a smoking cessation aid has become more popular than any other aid. Previous research suggests that ex-smokers from lower social groups are more likely to use e-cigarettes compared to ex-smokers from more socially advantaged groups. The present study aimed to assess the association between baseline education, income and employment status and (1) baseline motivation to stop using e-cigarettes (2) attempts to stop using e-cigarettes during follow-up among current smokers, recent ex-smokers and long-term ex-smokers who use e-cigarettes. Methods: UK online longitudinal survey of smokers, ex-smokers and e-cigarette users, May/June 2016 (baseline) and September 2017 (follow-up). In logistic regression models, motivation to stop using e-cigarettes at baseline (n = 994) and attempts to stop using e-cigarettes at follow-up (n = 416) among current smokers and ex-smokers were regressed onto baseline educational attainment, income, employment status while adjusting for baseline demographics, vaping status, smoking and e-cigarette dependence. Results: (1) Respondents with higher education (OR = 1.36; 95% CI: 1.06–1.74) or higher income (OR = 1.52; 95% CI: 1.17–1.98) were more likely to be motivated to stop using e-cigarettes, but only in unadjusted analysis. (2) Again, in unadjusted analysis only, employment was associated with reduced odds of attempting to stop using e-cigarette (OR = 0.50; 95% CI: 0.32–0.79). Conclusion: Higher socio-economic status may be associated with higher motivation to stop vaping but with lower likelihood of trying to do so.